Pengembangan RPW (Rahmat, Pisa, Wanti) Exercise terhadap Fisioterapi Neuromuskular - Hasmar, Wanti; Sugiarto, Rahmat; Napisah, Sri; Puad, Laylin; Pratama, Rini Mustikasari Kurnia; Rahayu, Umi Budi; Effran, Endy (Universitas Baiturrahim, 2025)
RPW Exercise is concepts found​ And developed by physio Rahmat , Pisa, Wanti . RPW exercise concept new And Not yet someone is researching previously . Concept This developed with modification from a number of new bobath concept theory based on by cerebral and reticular formation (postural). Theory draft This relate with body human beings were created by Allah SWT already very perfect , where moment happen something that makes Sick on body , there is the antidote And can repair Alone or called self-healing . RPW Exercise activates receptors vegetative , fascia, cerebral, corpus callosum, BDNF, reticular formation, broca's area , with AGA and AGB movements in general simultaneously in One movement . Design study This is Research and Development (R&D). Development of RPW Exercise to Play Store, test validation product by physiotherapy expert And technology informatics , then revision product , test try product group small 30 respondents use purposive sampling technique at Abdul Manap Regional Hospital And revision product , group big 50 respondents in Practice Independent Ftr Grace Sugiarto And revision product , then Implementation of RPW Exercise. Results Study with use test Paired Samples T-Test on RPW exercise on group small (n=30) of 0.000, then significant . Group big of 0.000, then significant . There is effectiveness of RPW Exercise on disturbance neuromuscular